Triune God : incomprehensible but knowable - the philosophical and theological significance of St Gregory Palamas for contemporary philosophy and theology /: incomprehensible but knowable - the philosophical and theological significance of St Gregory Palamas for contemporary philosophy and theology. ([2015]) - Unknown
No abstract available